The role of tubular cells in the pathogenesis of Fabry nephropathy - Rozenfeld, Paula; Feriozzi, Sandro; Braun, Fabian (Frontiers in Cardiovascular Medicine, 2024)
The pathophysiology of Fabry nephropathy (FN) is induced by galactosidase A deficiency with a chronic exposure of glycolipids to every lineage of renal cells. Tissue damage is attributed to the activation of molecular pathways, resulting in tissue fibrosis and chronic kidney disease. Podocytes have been the primary focus in clinical pathophysiological research because of the striking accumulation of large glycolipid deposits observable in histology. Yet, the tubular interstitium makes up a large portion of the whole organ, and therefore, its role must be further considered in pathogenic processes. In this review, we would like to propose Fabry tubulopathy and its ensuing functional effects as the first pathological signs and contributing factors to the development of FN. We will summarize and discuss the current literature regarding the role of tubular cells in Fabry kidney pathophysiology. Starting from clinical and histological evidence, we will highlight the data from animal models and cell cultures outlining the pathophysiological pathways associated with tubular interstitial injury causing renal fibrosis in Fabry nephropathy.